2008
DOI: 10.1002/ajhb.20797
|View full text |Cite
|
Sign up to set email alerts
|

Social stressors, mental health, and physiological stress in an urban elite of young Afghans in Kabul

Abstract: Afghanistan provides a unique setting in which to appraise psychosocial stress, given the context of persistent insecurity and widening economic inequality. In Kabul, people experience widespread frustrations, hinging on restricted opportunities for social advancement, education, and employment. We appraised social aspirations, every-day stressors, psychosocial distress, and mental health problems for a random sample of 161 male and female students at Kabul University. The survey featured both existing and new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
77
2
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(92 citation statements)
references
References 29 publications
8
77
2
3
Order By: Relevance
“…Researchers have found elevations in EBV antibody levels among individuals in poor quality marriages (Kiecolt-Glaser et al, 1993, caregivers for a family member with Alzheimer's disease (Kiecolt-Glaser et al, 1987), and Samoan adolescents and indigenous Siberian adults exposed to Westernizing influences (McDade et al, 2000b;Sorensen et al, 2009). Research in the US and internationally also indicates important gender differences, with higher levels of psychosocial stress and depression corresponding with elevated EBV antibody levels among women and adolescent girls (Kiecolt-Glaser et al, 1993;McDade & Worthman, 2004;Panter-Brick, et al, 2008).…”
Section: Psychosocial Stress and Immune Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers have found elevations in EBV antibody levels among individuals in poor quality marriages (Kiecolt-Glaser et al, 1993, caregivers for a family member with Alzheimer's disease (Kiecolt-Glaser et al, 1987), and Samoan adolescents and indigenous Siberian adults exposed to Westernizing influences (McDade et al, 2000b;Sorensen et al, 2009). Research in the US and internationally also indicates important gender differences, with higher levels of psychosocial stress and depression corresponding with elevated EBV antibody levels among women and adolescent girls (Kiecolt-Glaser et al, 1993;McDade & Worthman, 2004;Panter-Brick, et al, 2008).…”
Section: Psychosocial Stress and Immune Functionmentioning
confidence: 99%
“…A trend finding provides preliminary support for an association between discrimination-related stress and family support: the greater the stress women reported feeling because of negative things said to them, the more they agreed with the statement, 'when there are problems, you can count on family ' (r=0.26; p=0.07). Other plausible alternatives for these apparent gender differences are that women have different outlets for stress responses than men, such as depression or changes in eating behaviour (Flores et al, 2008), or that women's biology may moderate stress responses differently than men's (Panter-Brick et al, 2008).…”
Section: Perceiving Stress: Discrimination Acculturation and Physiolmentioning
confidence: 99%
See 1 more Smart Citation
“…48,69 Another study in Kabul showed the significant hypertensive cases (14.33%) among university students. 70 Risk factors like hypertension, diabetes and coronary artery diseases were also found to be highly prevalent in Afghani population. 71 According to WHO data 2011, age adjusted stroke death rate in Afghanistan was estimated to be 109.47 per 100,000 of population.…”
Section: Afghanistanmentioning
confidence: 99%
“…Anecdotal evidence suggests that Afghanistan is headed down this path with young people pushed into drug trafficking or joining the insurgency, solely to earn an income [11] or others giving up and deciding to leave the country in search of better opportunities. Many educated, urban youth are disillusioned and distressed as a result limited opportunities for social advancement and upward mobility [12], a consequence of a broken economy and a culture of pervasive nepotism instituted by those in positions of power [13]. Maley [14] contends that changing this situation and challenging the elites currently in positions of power can only occur by engaging with young people who remain committed to building a better future for themselves and their country.…”
Section: Introductionmentioning
confidence: 99%